A new species of Neocteniza Pocock 1895 (Araneae, Idiopidae) from Brazil - Bertani, Rogério; Fukushima, Caroline Sayuri; Nagahama, Roberto Hiroaki (Zootaxa, 2006)
Neocteniza myriamae n. sp. is newly described from Brazil. This species belongs to the australis group, which contains species with a small apical hematodocha on the male palpal bulb, with a thicker embolus, and without an apophysis on the apical sclerite. The new species is distinguished from N. australis and N. toba by the male embolus, which is thicker in its middle portion. From N. chancani, it can be distinguished by the larger size, elongated femur I, and especially by the presence of one conical keel and two parallel, well-developed keels on the apical half of the embolus.